The social construction of teacher and learner identities in medicine and surgery. - Cantillon, Peter; De Grave, Willem; Dornan, Tim (Medical Education, 2022)
Introduction: There are growing concerns about the quality and consistency of postgraduate clinical education. In response, faculty development for clinical teachers has improved formal aspects such as the assessment of performance, but informal work‐based teaching and learning have proved intractable. This problem has exposed a lack of research into how clinical teaching and learning are shaped by their cultural contexts. This paper explores the relationship between teacher–learner identity, educational practice and the workplace educational cultures of two major specialties: internal medicine and surgery. Methods: This was a secondary analysis of a large dataset, comprising field notes, participant interviews, images and video‐recordings gathered in an ethnographic study. The lead author embedded himself in four clinical teams (two surgical and two medical) in two different hospitals. The authors undertook a critical reanalysis of the observational dataset, using Dialogism and Figured Worlds theory to identify how teachers and postgraduate learners figured and authored their professional identities in the specialty‐specific cultural worlds of surgery and internal medicine. Results: Surgery and internal medicine privileged different ways of being, knowing and talking in formal and informal settings, where trainees authored themselves as capable practitioners. The discourse of surgical education constructed proximal coaching relationships in which trainees placed themselves at reputational risk in a closely observed, embodied practice. Internal medicine constructed more distal educational relationships, in which trainees negotiated abstract representations of patients' presentations, which aligned to a greater or lesser degree with supervisors' representations. Conclusions: Our research suggests that clinical education and the identity positions available to teachers and learners were strongly influenced by the cultural worlds of individual specialties. Attempts to change work‐based learning should be founded on situated knowledge of specialty‐specific clinical workplace cultures and should be done in collaboration with the people who work there, the clinicians. Cantillon et al. explore how clinical teaching and learning are uniquely shaped by the specialty‐specific cultures of postgraduate training.